Adverse events among adult Medicaid enrollees with opioid use disorder and co-occurring substance use disorders. (1st April 2021) - O'Brien, Peggy; Henke, Rachel Mosher; Schaefer, Mary Beth; Lin, Janice; Creedon, Timothy B.
Highlights: Adults misusing both opioids and other drugs had higher risk of adverse events. Risk for adverse events varied in magnitude by substance use disorder combination. Those misusing opioids and other drugs were more likely to have a mental disorder. Multisubstance use should be screened for and treated to prevent adverse events. Abstract: Background: It is common for adults with opioid use disorder (OUD) to misuse additional substances, and these individuals may be particularly at risk for adverse events, including mortality. Less is known about how continued receipt of prescription opioids or risk of adverse events (e.g., suicidality, overdose, poisoning) differs for people with co-occurring OUD and additional substance use disorders (SUDs). Methods: We conducted a retrospective study using IBM® MarketScan® Multi-State Medicaid Database enrollment/claims data. We used logistic regression to measure the association between sample characteristics and our dependent variables. The sample consisted of non-Medicare-eligible adults aged 18–64 years who were continuously enrolled in Medicaid in 2016–2017 with an OUD diagnosis on at least one claim in 2016. Results: Adults with OUD and a co-occurring SUD were more likely than adults with OUD only to have an opioid-related poisoning event (odds ratio [OR] = 1.488, p = .0052), all-cause poisoning (OR = 1.756, p < .0001), or suicidal ideation (OR = 1.796, p < .0001) but not to receive ongoing opioid prescriptions (OR = 0.973, p = .1626). Adverse events varied by OUD-SUD combination. For example, adults with OUD and cocaine use disorder had the highest odds of all-cause (OR = 2.393, p < .0001) or opioid-related (OR = 1.890, p = .0027) poisoning among those with a drug-specific diagnosis and were most likely to be diagnosed with suicidal ideation (OR = 2.465, p < .0001). Conclusions: This study provides evidence that adults with OUD and a co-occurring additional SUD have increased risk for several adverse events. Multisubstance use should be screened for and identified to determine the most appropriate course of treatment.